Peningkatan Kompetensi Bahasa Inggris, Penguatan Manajemen Kewirausahaan, Strategi Manajemen Pemasaran, dan Literasi Hukum bagi Siswa SMK - Muhamad Alfi Khoiruman; Galih Satriyo; Janoko Janoko; Suwarso Suwarso; Doni Hadi Irawan; Yosi Mulyana Pratiwi; Moehammad Robith Nahdi (Jurnal Medika: Medika, 2026)
The increasingly competitive labor market requires vocational high school graduates to possess not only technical skills but also foreign language proficiency, entrepreneurial competence, marketing knowledge, and legal literacy. This community service program aimed to enhance English language competence, strengthen entrepreneurship management, develop marketing management strategies, and improve legal literacy among students of SMK Sritanjung Banyuwangi. The methods employed included training sessions, educational workshops, interactive discussions, case studies, and participant mentoring. The materials covered English communication for professional purposes, basic business management, digital marketing strategies, and fundamental legal concepts related to employment and business activities. The results indicated an improvement in students’ knowledge and skills across all four areas. Participants demonstrated high engagement throughout the program and showed better abilities in English communication, business planning, marketing strategy development, and understanding basic legal aspects relevant to the workplace and entrepreneurship. This program contributed positively to preparing vocational students to become more competent, adaptive, and ready to face the challenges of employment and entrepreneurship in the era of globalization.